Effect of a sizing agent on short carbon fiber production with radial chopping technology. Issue 15 (August 2018) - Lu, Longsheng; Hou, Zhaorui; Zhang, Feixiang; Liu, Huilong; Chen, Songmao; Tang, Yong
Short carbon fiber (short-CF) has been extensively used as enforcement in composites or conductors in fibrous network materials, owing to its good subsequent processing compatibility with routine manufacturing technologies. Conventionally, short-CFs were made by cutting continuous CF-tows from thousands of meters into several millimeters length scale using a radial chopping technology, mainly through sizing, drying and chopping processes in sequence. In this work, four kinds of CF-tows with different physical properties were chopped to study the effect of a sizing agent on the production of short-CFs, including product morphology and yield ratio. All experiments were conducted on polyacrylonitrile-based CFs sized by polyurethane (PU)-acetone solution. Results show that the uniformity (an important index of short-CF appearance) of short-CFs is closely related to the unit sizing weight. The yield ratio is affected by the relative sizing amount of PU coated on CF-tows. In addition, a raw CF-tow with little fiber hairiness is beneficial to increase the yield ratio of short-CFs.